INetModels 2.0: an interactive visualization and database of multi-omics data. Issue Volume 49:Issue W1(2021) (13th April 2021) - Arif, Muhammad; Zhang, Cheng; Li, Xiangyu; Güngör, Cem; Çakmak, Buğra; Arslantürk, Metin; Tebani, Abdellah; Özcan, Berkay; Subaş, Oğuzhan; Zhou, Wenyu; Piening, Brian; Turkez, Hasan; et al.
Abstract: It is essential to reveal the associations between various omics data for a comprehensive understanding of the altered biological process in human wellness and disease. To date, very few studies have focused on collecting and exhibiting multi-omics associations in a single database. Here, we present iNetModels, an interactive database and visualization platform of Multi-Omics Biological Networks (MOBNs). This platform describes the associations between the clinical chemistry, anthropometric parameters, plasma proteomics, plasma metabolomics, as well as metagenomics for oral and gut microbiome obtained from the same individuals. Moreover, iNetModels includes tissue- and cancer-specific Gene Co-expression Networks (GCNs) for exploring the connections between the specific genes. This platform allows the user to interactively explore a single feature's association with other omics data and customize its particular context (e.g. male/female specific). The users can also register their data for sharing and visualization of the MOBNs and GCNs. Moreover, iNetModels allows users who do not have a bioinformatics background to facilitate human wellness and disease research. iNetModels can be accessed freely at https://inetmodels.com without any limitation. Graphical Abstract: